Integrating PBL, Ethno-STEM, and AR for Critical Thinking and Digital Literacy: A Systematic Review (2016–2025) - Amanah, Prelia Dwi; Rahayu, Satutik; Gunawan, Gunawan; Doyan, Aris (Pascasarjana, Mataram University, 2025)
This study aims to describe research trends related to the integration of Problem-Based Learning (PBL), Ethno-STEM, and Augmented Reality (AR) in improving students' critical thinking skills and digital literacy during the period 2016 to 2025. The formulation of the problem in this study is how the development of scientific publications related to the integration of the three approaches and their contribution to strengthening 21st century skills. The method used is descriptive analysis with a bibliometric approach using data from Google Scholar analyzed through Publish or Perish (PoP), Dimensions.ai, and visualized using VOSviewer. The results of the study show a significant increasing trend in publications discussing the integration of PBL, Ethno-STEM, and AR, especially since 2022, as well as the dominance of publications in the form of book chapters. In addition, keyword visualization confirms that the theme of developing innovative learning models, critical thinking, and digital literacy is the main focus in modern science education research. This study recommends further development of the integration of contextual and technological approaches to support improving the quality of learning in the digital era.